'It is Our Film': Rethinking Australian Postwar Cinema. Issue 2 (2nd April 2020) - Barnett, Chelsea
Abstract : The dominant narrative in Australian film historiography declares that the postwar period is unworthy of scholarly attention, particularly in contrast to the 'renaissance' of the 1970s. For historians working on twentieth-century Australian film production, the postwar years were a time in which very few Australian-authored films were made and released, and very few Australian people bothered to see them. This article intervenes into this narrative, and argues that the postwar era was a time of cinematic activity and audience engagement. It contends that the 1970s notion of 'cultural nationalism' has anachronistically shaped the majority of Australian film historiography, and instead argues for a new approach to Australian postwar cinema shaped by the new cultural history emphasis on historical specificity.